The Constitution of Water Power: Agro-exporters and groundwater scarcity in the Ica Valley and Pampas de Villacurí - Damonte Valencia, Gerardo (2016)
The agro-export boom in the coastal region of Ica has caused two interrelated processes: the generation of water scarcity scenarios and the emergency of the agro-exporter group as a new social actor. The role assigned to agro-exporters in the narrative of regional development has given them a dominant position in the management of Ica water resources. This has generated a re-configurationof social and political relationships at the local space that has allowed them to be able of even contest State’s efforts to regulate groundwater use. Thus, the questions guiding this research are: how the agro-exporter group has concentrated water power in Ica? And how do they exercise this power? This paper argues that control over groundwater resources has fallen into the hands of the agro-exporter group due to their capacity to concentrate and exercise three dimensions of power: economic capacity, technical knowledge and coercion. In developing this argument, we explain how the concentration of these power dimensions has influenced in the production of water scarcity scenarios to certain groups of population, without confronting much resistance despite of it.